2022
DOI: 10.3390/plants12010073
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrients Improve Growth and Development of HLB-Affected Citrus Trees in Florida

Abstract: Enhanced nutritional programs (ENPs) have improved citrus trees’ growth and development in the era of Huanglongbing (HLB). Studies conducted with variable rates of manganese (Mn) and Iron (Fe) on young HLB-affected citrus trees showed that applying double the standard recommendation increased growth and biomass accumulation. Since HLB is believed to cause deficiency symptoms of micronutrients in citrus trees, it is critical to ensure their optimal levels in the leaves. This could be achieved by soil applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…In a recent review by Alfaro et al [ 17 ], it was concluded that citrus rootstocks influence the quality of citrus fruits; however, few studies have focused on the assimilation of nutrients by rootstocks or on the corresponding translocation of nutrients through the rootstock/cultivar union. More recently, the particular importance of Fe in citrus was demonstrated, since the application of Fe(II) could restore the growth of trees affected by citrus greening or Huanglongbing (HLB), one of the most serious citrus diseases in the world [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review by Alfaro et al [ 17 ], it was concluded that citrus rootstocks influence the quality of citrus fruits; however, few studies have focused on the assimilation of nutrients by rootstocks or on the corresponding translocation of nutrients through the rootstock/cultivar union. More recently, the particular importance of Fe in citrus was demonstrated, since the application of Fe(II) could restore the growth of trees affected by citrus greening or Huanglongbing (HLB), one of the most serious citrus diseases in the world [ 18 ].…”
Section: Introductionmentioning
confidence: 99%